Enzymatic hydrolysis of starch by using a sonifier - Apar, Dilek Kilic; Turhan, Meltem; Ozbek, Belma (TAYLOR & FRANCIS INC, 2006)
In the present study, the ultrasonication method was used to investigate the effect of ultrasonic energy on the hydrolysis of corn, rice, and wheat starch by using the alpha-amylase enzymes produced by Bacillus species and Bacillus licheniformis . The effects of sonifier operation variables such as duty cycle and acoustic power rate on the stability of alpha-amylase enzymes and hydrolysis degrees of three types of starches were investigated at a temperature of 40 degrees C and pH 6.5. To determine the effect of temperature with sonication on the hydrolysis process, wheat starch hydrolysis experiments were also carried out at a temperature of 50 degrees C. Then, the relation between duty cycle and enzyme stability during hydrolysis for each enzyme at 50 degrees C was expressed by a zero-order inactivation model.
Keywords: alpha-amylase; enzyme stability; starch hydrolysis; sonication process; duty cycle; acoustic power; ULTRASOUND; ENZYMES; Engineering